Towards Promoting Rural Infrastructure for Poverty Reduction: Analysis of FADAMA III Small-scale Community-owned Infrastructure in Kaduna and Sokoto States, Nigeria (Journal of International Studies, 2019)
This study is aimed at assessing the impacts of Third National Fadama Development Project (NFDP III) on provision of Small-scale Community-owned Infrastructures (SCIs) for poverty reduction. The sector goal of NFDP III was to reduce poverty by improving the living conditions of the rural poor; contribute to food security and increase access to rural infrastructure. The study made use of questionnaires to generate primary data from 245 respondents whilst Project Implementation Manuals, Appraisal Reports, Baseline and Midline Surveys, etc constituted the secondary data. The study found out that outcomes of NFDP III had profound impacts on the incidence of poverty of the beneficiaries. For example in Kaduna State, incomes of Crop farmers increased by 199% and Livestock owners by 221%. In Sokoto State, the incomes of Crop farmers increased by 225% and Livestock owners by 315%. The food security situation of about 84.4% and 98.3% of the beneficiaries had improved, greatly and the socio-economic conditions of 74.2% and 95.7% of the beneficiaries had been promoted, significantly. The study recommends that to further sustained the impetus created by NFDP III on poverty reduction in Nigeria, the Federal, States and Local Governments should as a matter of concern, extend their commitments beyond those of facilitating the provision of rural infrastructure to those of scaling-up the levels of provision, maintenance and management and poverty reduction should ever remain part of national development goals.